Ion source and oscilloscope for Bendix Mass Spectrometer - Bendix Corporation (1970)
Assorted views of the ion source and oscilloscope designed for use with the Bendix Time-of-Flight Mass Spectrometer. One of four component parts of a mass spectrometer, the ion source produces a beam of particles characteristic of the sample material for qualitative and quantitative analysis. An oscilloscope is a laboratory instrument commonly used to display and analyze the waveform of electronic signals, in effect drawing a graph of the instantaneous signal voltage as a function of time. The Time-of-Flight Mass Spectrometer (TOFMS) was the flagship analytical instrument of the Bendix Corporation.
Keywords: Oscilloscopes; Scientific apparatus and instruments; Spectrometer industry; Mass spectrometry; Time-of-flight mass spectrometry; Bendix Corporation; Ion sources; Mass spectrometers